Can Serious Injury in Professional Football be Predicted by a Preseason Functional Movement Screen? - Kiesel, Kyle (Sports Physical Therapy Section, APTA, 2007)
BACKGROUND: Little data exists regarding injury risk factors for professional football players. Athletes with poor dynamic balance or asymmetrical strength and flexibility (i.e. poor fundamental movement patterns) are more likely to be injured. The patterns of the Functional Movement Screen(™) (FMS) place the athlete in positions where range of motion, stabilization, and balance deficits may be exposed. OBJECTIVES: To determine the relationship between professional football players' score on the FMS(™) and the likelihood of serious injury. METHODS: FMS(™) scores obtained prior to the start of the season and serious injury (membership on the injured reserve for at least 3 weeks) data were complied for one team (n = 46). Utilizing a receiver-operator characteristic curve the FMS(™) score was used to predict injury. RESULTS: A score of 14 or less on the FMS(™) was positive to predict serious injury with specificity of 0.91 and sensitivity of 0.54. The odds ratio was 11.67, positive likelihood ratio was 5.92, and negative likelihood ratio 0.51. DISCUSSION AND CONSCLUSION: The results of this study suggest fundamental movement (as measured by the FMS(™)) is an identifiable risk factor for injury in professional football players. The findings of this study suggest professional football players with dysfunctional fundamental movement patterns as measured by the FMS(™) are more likely to suffer an injury than those scoring higher on the FMS(™).